Village Savings and loan associations and socio-economic empowerment of vulnerable people in Kamuganguzi Sub-County Kabale, District, Uganda. - Deus, Mwijukye; Moses, Agaba (International Journal of Development Research, 2020)
The study carried out was entitled “Village Savings and Loan Associations (VSLA) and socioeconomic empowerment of vulnerable people in Kamuganguzi Sub County, Kabale District. According to UBOS 2018, Kamuganguzi Sub County which was the study area was among the poorest sub counties of Ndorwa County, Kabale District where a total of 3,516 people were food insecure, 769 people had no access to safe water, 691 children (6-17years) were out of school, 1,142 children were involved in child labour and 110 children were currently married. Village Savings and Loan Association (VSLA) was promoted in Kamuganguzi Sub County by LADA Uganda to empower vulnerable households economically however, information as to whether their socio-economic status was improved was still sketchy and lacking. It was therefore necessary to carry out a study to fill the gap. The research design was cross-sectional in conjunction with qualitative and quantitative approaches. The tools for data collection were both the interviews and questionnaires. The study objectives included; determining the effect of savings on the socio-economic empowerment of vulnerable people, examining the relationship between credit access and socio-economic empowerment of vulnerable people, and examining the effect of social fund on socio-economic empowerment of vulnerable people in Kamuganguzi Sub County Kabale District. The study population was 255 which included LADA Uganda staff and VSLA group members. The key findings were; improving the health status of women in families; credit access and socio-economic empowerment of vulnerable people were synonymous with community replacing the damaged property. The conclusion was that village savings and loan associations and socio-economic empowerment of vulnerable people were found to be significantly related. The recommendations were; need to improving the health status of women in families as well as children since they are regarded vulnerable in order to let them live happily; there should be improved nutrition and food supply to all families to let children and other members grow healthy and live a happy life; increased household income should be the ultimate goal fostered by credit accessibility in the area which must be done with ease through the start of small and medium enterprises especially women; it is recommended that the vulnerable groups of people have the replacement of the damaged property in case of any loss aiming at keeping standards of living at household level; achieving flexibility to immense development of social capital required the development of the saving culture that promotes regular income to help the community solve their personal problems; the social fund should be a unifying factor that enhances development through increased social networking to allow information flow since information is power.